Use of nasal mucosa graft in tympanoplasty - Coelho,Sandro Barros (2022)
Abstract Introduction Tympanoplasty techniques with different types of graft have been used to close tympanic perforations since the 19th century. Tragal cartilage and temporalis fascia are the most frequently used types of graft. They lead to similar functional and morphological results in most cases. Although little published evidence is present, nasal mucosa has also been shown to be a good alternative graft. Objective Surgical and audiological outcomes at the six-month follow-up in type I tympanoplasty using nasal mucosa and temporalis fascia grafts were analyzed. Methods A total of 40 candidates for type I tympanoplasty were randomly selected and divided into the nasal mucosa and temporalis fascia graft groups with 20 in each group. The assessed parameters included surgical success; the rate of complete closure of tympanic perforation and hearing results; the difference between post- and pre-operative mean quadritonal airway-bone gap, six months after surgery. Results Complete closure of the tympanic perforation was achieved in 17 of 20 patients in both groups. The mean quadritonal airway-bone gap closures were11.9 and 11.1 dB for the nasal mucosa and temporalis fascia groups, respectively. There was no statistically significant difference between the groups. Conclusion The nasal mucosa graft can be considered similar to the temporal fascia when considering the surgical success rate of graft acceptance and ultimate audiological gain.